Gross Anatomical Study on the Mandible of Rhesus Monkey (Macaca mulata) - Verma, Abhinov; Pathak, Archana; Farooqui, M.M.; Prakash, Ajay; Singh, S.P.; Pandey, R.P. (Indian Journal of Veterinary Anatomy, 2022)
The present investigation was conducted on the mandible of adult rhesus monkey (Macaca mulata). The carcass of monkey was procured from the veterinary clinical complex, Mathura. It was macerated, cleaned and washed to procure the bones. All the bones were well identified in the skull of monkey. The mandible or lower jaw bone was studied with it functional importance and application in forensic science. Two halves of mandible were completely fused together and a faint line demarcate the place of fusion. The intermandibular space was ’V’ shaped. Body of mandible had alveoli for 04 incisors and 02 well developed canine teeth. The horizontal ramus had 02 premolar and 03 molar teeth.The mental foramen was present below the 2nd premolar tooth in horizontal ramus. The coronoid process was thin plate like directed upward and projecting outward. An oblique ridge was noticed between mandibular foramen and coronoid process. The condyles were elongated transversely and extended caudoventraly. The neck of mandible was indistinct. The mandibular notch was shallow in rhesus monkey.